PERANCANGAN MEJA PUTAR ROLL WELDING SEBAGAI ALAT BANTU PENGELASAN (STUDI KASUS : ART WELDING PT. MECO INOXPRIMA) - Imam kholiq Imam Imam (Matrik : Jurnal Manajemen dan Teknik Industri Produksi, 2019)
Welding that produces a quality connection and is very possible to connect metal by welding in various shapes and positions. Therefore the welding process must require a practical material supporting device and in accordance with the needs of all welding positions which will facilitate and provide welder comfort in welding. So that the results of maximum and quality welds (good hasis las visually) are produced in this study the type of connection used is angular joints with the aim of designing and making tools to get the results of welding joints and comparing the distortions that occur between using desk tools rotate and without using tools. In this study Gtaw welding was used with the brand DC ARC WELDER with type Bz-300F-3 and filler type ER 308L, Voltage 20-30 V, travel speed 60 mm / min and variations of Flow (A) namely 100 A, 125 A and 150 A. with a diameter of 2.4 mm as a filler. The study was limited to the design and manufacture of tools and measurements of distortion carried out 20 times. Distortion measurement uses a dial indicator with a starting point / zero point on the end of the test object and the end point in the weld joint area. The results show that the use of roll welding tools can reduce the occurrence of distortion. The smallest value of distortion is obtained using a roll welding rotary table tool which is equal to 0.33 degrees, while the smallest value of distortion without using roll welding is 1.33 degrees. And the use of roll welding rotary table aids can reduce welding defects reduce setup time and can increase production volume which results in a decrease in production costs, making it quite feasible and efficient in terms of the economy.